Nonlinear PI controllers with output transformations. Issue 12 (25th August 2015) - Lee, Jietae; Edgar, Thomas F.
Abstract : Well‐designed nonlinear proportional‐integral (PI) controllers are successful for nonlinear dynamical processes like linear PI controllers are for linear processes. Two nonlinear blocks representing proportional and integral terms can be designed so that the linearized controllers perform the same as linear PI controllers for linearized processes at the given operating points. For some nonlinear processes, nonlinear blocks for nonlinear PI controllers can be singular at some operating points, and control performances can be poor for set points near those points. To mitigate such disadvantages, new nonlinear PI controllers that introduce output transformations are proposed. Several examples are given, showing the performance of the proposed nonlinear PI controllers. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4264–4269, 2015